Lung cancer Detected as a Metachronous Second Primary Malignancy in a patient with Pyriform Sinus Carcinoma during 18F FDG PET-CT scan - Mandal, Tapati; Mutsuddy, Pupree; Siddique, Abu Bakker; Begum, Shamim MF (Bangladesh Journal of Nuclear Medicine, 2022)
Pyriform sinus squamous cell carcinoma is the most prevalent type of hypopharyngeal carcinoma. The presence of a second primary malignancy in pyriform sinus carcinoma is uncommon. We present a case of metachronous second primary lung cancer detected by whole-body 18F-FDG PET-CT imaging during the follow-up evaluation in a treated case of well-differentiated squamous cell carcinoma of the left pyriform fossa. Bangladesh J. Nuclear Med. 24(1&2): 64-67, 2021